Reversal Modes in Small Rings: Signature on the Susceptibility - Altbir-Drullinsky, D; Baltazar-Rojas, S; Allende-Prieto, S; Escobar-Donoso, R; Vargas-Ayala, N; Castillo-Sepulveda, S (American Institute of Physics, 2014)
The magnetization reversal mechanisms of small rings have been investigated as a function of the geometry. Stepped and non stepped hysteresis loops were obtained and four different reversal mechanisms were identified. In spite the important information that is possible to get from the hysteresis loops, in some cases it is not possible to identify from them the reversal mechanisms. However, susceptibility curves deliver enough information to determine precisely the reversal mode, making these curves a valuable tool for the study of the magnetization reversal in rings. © 2014 AIP Publishing LLC.